Mortalidade materna por cardiopatia Maternal mortality due to heart disease - Helvécio N. Feitosa; Antônio F. Moron; Daniel Born; Pedro Augusto Marcondes de Almeida (Universidade de São Paulo, 1991)
Realizou-se estudo retrospectivo da mortalidade materna por cardiopatia, no período de janeiro de 1979 a dezembro de 1989. Dentre um total de 16.423 internações, houve 694 gestantes com o diagnóstico de cardiopatia (4,2%). No mesmo período, ocorreram 51 óbitos maternos, correspondendo a um coeficiente de mortalidade materna de 428,2/100.000 nascidos vivos. Houve 12 óbitos maternos por cardiopatia. A análise estatística permitiu a identificação de alguns fatores associados a maior risco de morte nas pacientes cardiopatas: primeira gravidez, primiparidade, ausência de assistência pré-natal, realização de cirurgia cardíaca anterior à gravidez e/ou na gestação. O maior número de mortes ocorreu no puerpério. A classificação funcional (NYHA) não se constituiu em parâmetro seguro para avaliar o prognóstico materno, pois 91,7% dos casos de óbito foram incluídos no grupo considerado favorável (classes I e II) ao iniciar a gestação. A retrospective study on maternal mortality in pregnant women with cardiac disease over a period of eleven years (January 1979 to December 1989) was undertaken. The objetive was an analysis of the main aspects of this association. Cardiac disease was diagnosed in 694 patients (4.2%) of a total of 16,423 admitted to the Obstetrics Department of the Escola Paulista de Medicina. As for etiology, rheumatic disease (52.3%); Chagas's disease (19.3%) and congenital disease (8.1%) were the most frequent causes. There were 51 maternal deaths, according to FIGO's definition (1967), corresponding to a maternal mortality rate of 428.2/100,000 livebirths during the same period. Twelve of these maternal deaths were due to cardiac disease (maternal mortality rate of 100.8/100,000 livebirths). The statistical analysis identified the following aspects associated with maternal mortality among patients with cardiac disease: primigravida, lack of adequate prenatal care, and cardiac surgery performed previously to and/or during pregnancy. Congestive heart failure with pulmonary edema (41.7%) and thromboembolism (25.0%) were the most frequent causes of maternal death among patients with cardiac disease. The NYHA functional classification was not a good parameter for pregnancy prognosis: eleven patients (91.7%) were considered as belonging to the favorable group before they became pregnant. Most maternal deaths occurred during the first 72 hours after delivery. Therefore, this period was considered most critical for maternal mortality in patients with cardiac disease. No relation-ship was found among the factors: maternal age, race, marital status, delivery and maternal mortality among patients with cardiac disease. The effects of maternal death on the prognosis of the fetus and newborn were severe: 1/3 were undelivered; 1/2 premature liveborn, one fetus died during delivery and an other in the neonatal period. Thus a loss of 50.0% of the conceptuses occurred in this group.